Beyond the River Chebar studies in kingship and eschatology in the book of Ezekiel - Block, Daniel Isaac 1943- (Cambridge, England James Clarke & Co, 2014)
7. The Literary Context of this Vision. 8. The Relationship between the Mosaic Torah and Ezekiel 40-48; 9. Fantastic and Stylized Elements in the Vision.; 10. The Influence of Ezekiel's Design on Later Writers.; Conclusion; 9. Guarding the Glory of YHWH: Ezekiel's Geography of Sacred Space; Introduction; The Land of Israel as Sacred Space; The Temple Compound as Sacred Space; Aesthetics and Function in Ezekiel's Design; Conclusion; Bibliography; Back Cover.
Conclusion7. Gog and the Pouring Out of the Spirit: Reflections on Ezekiel 39:21-29; Introduction; Recent Treatments of the Concluding Section; A Suggested Alternative Interpretation; The Significance of 39:21-29 in its Context; Conclusion; 8. Envisioning the Good News: Ten Interpretive Keys to Ezekiel's Final Vision; Introduction; 1. The Nature of the Text; 2. The Literary History of the Text; 3. The Historical Context of the Vision; 4. The Declared Genre of the Material; 5. Precursors to this New Temple Vision; 6. The Literary Structure of the Vision.
Ezekiel's View of Jehoiachin's PastJehoiachin's Future in Ezekiel; The Significance of Ezekiel's Portrayal of Jehoiachin; Conclusion; 4. Bringing Back David: Ezekiel's Messianic Hope; Introduction; Ezekiel 37:22-25; The 'Prince' in Ezekiel 40-48; 5. Gog and Magog in Ezekiel's Eschatological Vision; Introduction; General Observations on Ezekiel's Eschatology; The Nature and Design of the Gog Oracle; Summary Exposition; Conclusion; 6. Gog in Prophetic Tradition: A New Look at Ezekiel 38:17; Introduction; Nature and Design of the Gog Oracle; The Significance of 38:17 within the Gog Oracle.
Front Cover; Title page; Copyright; Contents; Illustrations; Preface; Acknowledgments; Credits; Abbreviations; 1. Zion Theology in the Book of Ezekiel; The Problem; The Explanation; 2. Transformation of Royal Ideology in Ezekiel; Introduction; Ezekiel's Portrayal of the History of Israel's Monarchy; Ezekiel's Portrayal of the Monarchy in His Day; Ezekiel's Portrayal of the Future of the Monarchy; My Servant David; The 'Leader' in Ezekiel 40-48; Conclusion; 3. The Tender Cedar Sprig: Ezekiel on Jehoiachin; Introduction; Jehoiachin's Name and Title; Jehoiachin's Story.
This book is a sequel to 'By the River Chebar: Historical, Literary, and Theological Studies in the Book of Ezekiel'. Like the studies in that volume, those presented here reflect the author's longstanding interest in Ezekiel, the man and his book. This collection is arranged as follows: a general essay on Zion theology; three studies related to Ezekiel's perception of kingship and the Messiah; three essays on the Gog oracle (Ezek 38-39); and two on Ezekiel's concluding vision (Ezek 40-48)
Includes bibliographical references
Keywords: Bible -- Criticism, interpretation, etc; Bible -- Theology; Bible; Kings and rulers -- Biblical teaching; Eschatology -- Biblical teaching; RELIGION ; Biblical Studies ; Prophets; RELIGION ; Christian Theology ; Eschatology; Eschatology ; Biblical teaching; Kings and rulers ; Biblical teaching; Theology; Criticism, interpretation, etc; Electronic books